(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تتميز محافظة إدلب بأنها تمتزج الطبيعة بالمعالم التاريخية الأثرية بتآلف واضح. وتشكل المعالم الأثرية ثروة وطنية والقاعدة الأساس لتطوير مختلف أشكال(أوجه) النشاط السياحي. وتتمثل هذه المعالم بمدنها المنسية التي هي إحدى الأوجه الثقافية- الأثرية في تاريخ المحافظة، وتضم محافظة إدلب تجمعات لمعالم أثرية على مستوى العالم في غاية الروعة والجمال، وعظمة في البنيان بسحرها المعماري، وتشكل المدن المنسية جزءاً مهماً من تاريخ سورية وتراثها المعماري، ورغم ذلك فهي لا تملك شهرة محلية وعربية وعالمية تتناسب مع أهميتها التاريخية والأثرية. لذا فإنه من الضروري تسليط الضوء على واقعها السياحي الراهن، واستشراف المستقبل الذي يمكن أن تكون عليه. The province of Idlib is Characterized by the mixture of nature with historical monuments in clear harmony, monuments represent national wealth and the fundamental basis for the development of various forms (aspects) of touristic activity, and it is represented by its forgotten cities one of the cultural – monumental aspects in the history of the province. It includes pools of archaeological monuments on world level, they are very magnificent. And grandeur in architecture charm nowhere else in parts of the world, and the forgotten cities are an important part of the history of Syria and its architectural heritage. Although, ther don,t have the local Arabic and international fame commensurate with the importance of historical and archaeological sites. So, it is necessary to shed light on, its present tourist state, Orientalism and the future that it could be.